Raw Silk Prices and the Business Cycle - Coyle, Eunice S. (The Review of Economics and Statistics, 1924)
HE repeated swings upward and downward which have been characteristic of raw silk prices in the last 25 years have ordinarily occurred at about the same time as similar movements in general business and some time after similar movements in stock speculation. The rough correspondence of raw silk prices to changes in general business is informing, but their lag after speculation has a more practical interest, since, if it persists in the future as in the past, movements of speculation should constitute a useful forecast of major movements of raw silk prices.